Maintenance of Granite-Clad Facades with Stainless Steel Screws and Chemical Anchoring: A Case Study of a Residential Building in Recife/PE - Silva, Rômulo Pereira da; Melo, Sérgio Henrique Soares; Sampaio, Allefy Teles; Monteiro, Eliana Cristina Barreto; Pinto, Roberta Richard (Technical and Scientific Journal Green Cities, 2025)
Objective - This article aims to present a case study on the maintenance of facades clad with granite slabs in a building located in Recife – PE, highlighting the importance of conservation in coastal areas with high environmental aggressiveness. Methodology - The research utilized visual inspections, mapping of infiltrations, percussion tests, and technical monitoring of the services, adopting as the main solution the securing of granite slabs through screws. Originality/Relevance - The study addresses a theoretical gap related to the maintenance of facades in aggressive environments, emphasizing the need for efficient practices for the preservation of both historical and contemporary buildings. Results - The main outcomes include the restoration of safety, durability, and watertightness conditions of the facades, demonstrating the effectiveness of the proposed solution. Theoretical/Methodological Contributions - The theoretical implications include the enhancement of knowledge about maintenance techniques for granite facades, while the methodological contributions reinforce the importance of systematic approaches in evaluating and intervening in buildings. Social and Environmental Contributions - The findings underscore the relevance of preserving architectural heritage for local cultural identity and promote awareness of the importance of sustainable actions in the conservation of buildings in coastal areas.